Saúde mental, luta antimanicomial e reforma psiquiátrica: o protagonismo das conferências nacionais de saúde e de saúde mental - Alves, Isadora de Souza (2019)
The research aims at mental health, anti-asylum and psychiatric reform, which resulted in the construction of the national mental health policy in 2001, with a major breakthrough in the indication of substitutive services. Treatment in mental health has historically been associated with isolation and inhuman treatment, where madness has always been considered as a risk to coexistence in society. However, in the capitalist system the relation of madness is closely linked to the notion of productivity since it does not meet the standards imposed by the social order of normality. The anti-asylum fight and the psychiatric reform project denounce this model of treatment and propose a perspective of mental health defense in its expanded conception and as a human right. The study assumes that the Social Work is a profession committed to the fight against anti-asylum and psychiatric reform, and must recognize the person in mental suffering as a subject of rights, as established in the Federal Constitution and the Unified Health System, with treatment humanized and quality that ensures their freedom. The research has as general objective to analyze the National Mental Health Policy and the protagonism of the subjects in the National Conferences of Health and Mental Health, from the Law of Psychiatric Reform n. 10,216 / 2001. And, as specific objectives, to reflect the anti-asylum struggle and the project of psychiatric reform; to identify the debate in the Social Service on the fight against anti-asylum and the medicalization of life and to analyze in the final reports of the National Conferences the contemporary conceptions and demands on mental health. From the perspective of totality the bibliographical and documentary research was constructed and presented through the qualitative approach for the understanding of the protagonism of the subjects and of the own madness. The results show that the psychiatric reform project faces, in the contemporary scenario, great challenges that require the participation in the spaces of the Conferences for the defense of the anti-asylum struggle in the country. Above all, they reveal that excessive medicalization is directly related to the influences of the pharmaceutical industry and can be understood as a new mode of isolation and pathologization of madness, therefore, it is shown as contemporary expressions of the social question in mental health.